O-022 Dual antiplatelet therapy after carotid artery stenting: trends and outcomes in a large national database. (4th August 2020) - Sussman, E; Jin, M; Pendharkar, A; Pulli, B; Feng, A; Heit, J; Telischak, N
Abstract : Introduction: Carotid artery stenting (CAS) is a safe and effective treatment for extracranial carotid artery atherosclerotic disease. While dual antiplatelet therapy (dAPT) is the standard of care following CAS, the optimal dAPT regimen and duration has not been established. Methods: We canvassed a large national healthcare claims database (IBM MarketScan) to identify patients receiving either carotid endarterectomy (CEA) or CAS for the primary indication of either ischemic stroke or carotid artery stenosis between 2007 and 2016. At least 6-months of continuous post-stent health care plan enrollment was required for inclusion. We performed univariable and multivariable regression methods to evaluate the impact of covariates on post-CAS stroke-free survival. Aggregate post-discharge antiplatelet (P2Y12 inhibitor) prescriptions were based on National Drug Code terminology and number of prescribed days during the 6-months following CAS. Results: In total, 79, 084 patients diagnosed with either ischemic stroke or carotid stenosis received either CEA (71, 178; 90.0%) or CAS (7, 906; 10.0%). After adjusting for available covariates, fewer than 180 days of prescribed post-CAS P2Y12 inhibition was associated with increased risk for stroke (<90 prescribed days HR=1.421, 95% CI 1.038–1.946; 90–179 prescribed days HR=1.484, 95% CI 1.045–2.106). The incidence of hemorrhagic complications was higher during the period of prescribed P2Y12 inhibition (1.16%/person-month vs 0.49%/person-month after discontinuation, p<0.001). The rate of extracranial hemorrhage was nearly 6-fold higher while on dAPT (6.50%/patient-month vs 1.16%/patient-month, p <0.001), and there was a trend towards higher rate of intracranial hemorrhage that did not reach statistical significance (5.09%/patient-month vs 3.69%/patient-month, p =0.0556). Later hemorrhagic events beyond 30 days post-CAS were significantly more likely to be extracranial than intracranial ( p =0.028). Discussion: Increased duration of post-CAS dAPT is associated with lower rates of readmissions for stroke, and with increased risk of hemorrhagic complications, particularly extracranial hemorrhage. The potential benefit of prolonging dAPT with regard to ischemic complications must be balanced with the corresponding increased risk of predominantly extracranial hemorrhagic complications. Further studies are warranted to determine the optimal post-CAS antiplatelet regimen and duration. Disclosures: E. Sussman: None. M. Jin: None. A. Pendharkar: None. B. Pulli: None. A. Feng: None. J. Heit: None. N. Telischak: None.